Harmoniser les pratiques éditoriales numériques des revues françaises d’archéologie - Stéphane Renault; Blandine Nouvel; Micaël Allainguillaume; Astrid Aschehoug; Nicolas Coquet; Marie-Adèle Turkovics (Humanités Numériques, 2020)
This article presents a project to harmonise the digital publishing policies of five archaeological journals in a context involving about forty editorial supports in the field in France. Taking advantage of the technological and documentary tools available for publishing, especially in archaeology and its related sciences, these journals have decided to update their practices by adopting a shared grammar and a shared corpus of keywords and by experimenting with new interoperable models for structuring and indexing their contents. They are thus nested in a scientific production chain that readily references publication and data together. The aim is to widen and facilitate access to scientific information.